Venture Capital Investment and Labor Market Performance: A Panel Data Analysis - Ansgar Belke; Rainer Fehn; Neil Foster (Center for Economic Studies and ifo Institute (CESifo), 2002)
Labor market performance has differed considerably between OECD countries over the last two decades. The focus of the literature so far has been to ask whether these differences can be explained by varying degrees of labor market rigidities and generosity of welfare states. This paper takes a different perspective and analyzes whether differences in venture capital investments have explanatory power with respect to labor market performance across countries and over time. In particular, the Anglo-Saxon countries have been relatively successful over the last two decades in producing employment growth and in reducing unemployment compared to most continental European OECD countries. As a rule they have also been and are still ahead in developing thriving venture capital markets that are often deemed crucial for the creation of new firms and for successfully managing the ongoing radical structural change away from traditional industrial production toward the so-called new economy.
Keywords: 330; labor markets; venture capital; unemployment; new economy; panel analysis.